High-resolution mapping and modeling of anammox recovery from recurrent oxygen exposure. (1st November 2018) - Seuntjens, D.; Carvajal-Arroyo, J.M.; Ruopp, M.; Bunse, P.; De Mulder, C.P.; Lochmatter, S.; Agrawal, S.; Boon, N.; Lackner, S.; Vlaeminck, S.E.
Abstract: Oxygen inhibits anammox, a bioconversion executed by anoxic ammonium oxidizing bacteria (AnAOB). Nonetheless, oxygen is mostly found in the proximity of AnAOB in nitrogen removal applications, being a substrate for nitritation. The experiments performed to date were mostly limited to batch activity tests where AnAOB activity is estimated during oxygen exposure. However, little attention has been paid to the recovery and reversibility of activity following aerobic conditions, of direct relevance for bioreactor operation. In this work, anoxic and autotrophic reactor cultivation at 20 °C yielded an enriched microbial community in AnAOB, consisting for 75% of a member of the genus Brocadia . High-resolution kinetic data were obtained with online ammonium measurements and further processed with a newly developed Python data pipeline. The experimentally obtained AnAOB response showed complete inhibition until micro-aerobic conditions were reached again (<0.02 mg O2 L −1 ). After oxygen inhibition, AnAOB recovered gradually, with recovery times of 5–37 h to reach a steady-state activity, dependent on the perceived inhibition. The recovery immediately after inhibition was lowest when exposed to higher oxygen concentrations (range: 0.5–8 mg O2 L −1 ) with long contact times (range: 9–24 h). The experimental data did not fit well with a conventional 'instant recovery' Monod-type inhibition model. Yet, the fit greatly improved by incorporating a dynamic growth rate formula accurately describing gradual activity recovery. With the upgraded model, long-term kinetic simulations for partial nitritation/anammox (PN/A) with intermittent aeration showed a decrease in growth rate compared to the instant recovery mode. These results indicate that recovery of AnAOB after oxygen exposure was previously overlooked. It is recommended to account for this effect in the intensification of partial nitritation/anammox. Graphical abstract: Image 1 Highlights: During oxygen exposure, anammox bacteria (AnAOB) showed no activity. Interestingly, the AnAOB activity recovered only gradually after oxygen exposure. The proposed model fitted the data better than the conventionally used model. The recovery impacts achievable removal rates for partial nitritation/anammox.